Clustered Regularly Interspaced Short Palindromic Repeats-Based Diagnostics and COVID-19; A Leap Forward in Molecular Pathology - Khan, Sikandar Hayat (Pakistan Armed Forces Medical Journal, 2023)
With emergence of COVID-19 threats various diagnostic strategies have also surfaced. Conventionally, the laboratory world used to rely on serological diagnosis but availability of molecular techniques, especially “Polymerase Chain Reaction” (PCR) has initially emerged as the front line test for diagnosing SARS-CoV2 infection. Though defined as the current mainstay of COVID-19 diagnosis, still the technology suffers with less diagnostic sensitivity and specificity along with prolong Various diagnostic strategies have also surfaced with the emergence of the COVID-19 threat. Conventionally, the laboratory world used to rely on serological diagnosis, but the availability of molecular techniques, especially “Polymerase Chain Reaction” (PCR), has initially emerged as the front-line test for diagnosing SARS-CoV2 infection. Though defined as the current mainstay of COVID-19 diagnosis, the technology still suffers from less diagnostic sensitivity and specificity and prolonged turnaround times (TAT). The recent emergence of novel techniques, i.e., CRISPR/Cas technologies, in diagnosing COVID-19 infection has been tremendous and provides newer replacements for PCR testing. CRISPR with Cas12 and Cas13 from CRISPR type-V and type-VI has the potential to revolutionize COVID-19 diagnosis due to better diagnostic efficiency, lower limits of detection (LOD), much-reduced turnaround times (TAT) and availability as point of care testing (POCT). Key technologies discussed in this include SHERLOCK, DETECTER, AIOD-CRISPR, PAC-MAN, CREST and others. This short communication briefly conceptualizes CRISPR/Cas, followed by a discussion on currently available CRISPR technologies for COVID-19 infection with an overview classification of most available methods.